Analisis Kesalahan I'rab dan Shigah pada Santri Miftahus-Sholihin Cimahi - Solehah, Mirna; Farhan, Muhammad (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to identify syntactic and morphological errors in third-year students of Madrasah Diniyah Takmiliyah (MDT) Miftahus-sholihin and provide treatments to reduce these errors. Given the international popularity of Arabic, it is essential to conduct research focusing on improving students' understanding of all aspects necessary for mastering the Arabic language. This research focuses on errors in syntactic and morphological aspects, categorized into three subcategories in syntax: 1) final harakat determination, 2) i`rab characteristics, and 3) sentence structure; and two subcategories in morphology: 1) initial and final harakat determination, and 2) shigah determination, totaling five subcategories. The study introduces a new approach to addressing Arabic language errors in syntactic and morphological aspects through the Focus Group Discussion (FGD) model. The findings highlight FGD's effectiveness in Arabic language education, particularly in reducing morphological shigah errors, with results showing a 5% reduction in error rates from 31% (170 errors) to 26% (141 errors). This research enhances Arabic teaching methods with FGD, promotes innovative strategies, and improves the curriculum. Further exploration of FGD and other innovative methods is recommended, along with longitudinal studies.